Pandopo Catering as a Medium for Student Community Service and Community Empowerment: Pandopo Catering sebagai Media Pengabdian Mahasiswa dan Pemberdayaan Masyarakat - Budi Djatmiko; Abshor Marantika; Muhamaad Rifat Syauqy; Sudadi Pranata; Lista Meria; Cicilia Sriliasta Bangun (ADI Pengabdian Kepada Masyarakat, 2025)
This community service project examines the role University of Raharja students in community service, focusing on efforts to foster social awareness and economic independence through the introduction of "Pandopo Catering" to local communities. The importance of community service as a means of social development, particularly in empowering local communities to achieve economic self-reliance. The objective of this research is to explore how the involvement of Raharja University students in community service, through innovative business initiatives such as Pandopo Catering, can promote social awareness and contribute to economic independence in underserved areas. The method used is a qualitative approach involving case studies and interviews with students and community members participating in the community service program. The results show that student participation in this program not only enhances social awareness among students but also helps local communities develop practical skills and entrepreneurial initiatives that can strengthen their economic resilience. Additionally, students gain hands-on experience in applying the knowledge acquired in the classroom. The conclusion of this research emphasizes that the involvement of Raharja University students in community service not only benefits the community but also contributes to the personal development of students, enhancing their sense of social responsibility and entrepreneurial mindset. This research provides insights into the potential of student-led initiatives in promoting sustainable development in local communities.